(untitled) - Ooi, Jin-Bee (London, 1976)
This text discusses the challenges of fishing industries in Peninsular Malaysia: the technology impact on fisheries, overfishing, biological and economic consequences, regulation, fish resource management, and more.
Keywords: Malaya,Malaya,Malaysia,Malaysia; History,Lịch sử,History,Lịch sử